Mundane Highways or Identity Rich Road Scape: An Element and Location Based Approach to Place Identity - G, Ophylia Vinodhini; Sundaram, A. Meenatchi (International Journal of Psychosocial Rehabilitation, 2020)
Visual perspective of people differs in perceptions and observations of drivers and travellers. The planning of pedestrian environment needs assumptions of how the pedestrians respond to features as they have their planned paths. Consequently, most research interest in public environments focuses on the behaviours of the pedestrians related to those features. There are picturesque and typological studies. Metric, geometric and topological models have established useful in identifying the density and direction of the movements. This paper addresses the social imperative to reconsider the value of features along roadside environment in direct elemental approach. The focus of the research is on thirteen shortlisted elements in a high capacity highway, in the culturally rich state of Tamilnadu, India. The elements such as signage, trees, washrooms, food joints and teashops are ranked based on a questionnaire survey (n=250). Statistical analysis helps to examine the equal probabilities of significance of elements with respect to their occurrences. The research characterizes elements based on natural, cultural, functional, and recreational characters. The functional elements are more significant to people as compared to rivers, historic structures, shrines etc. However, natural, cultural, or recreational elements are more vital for place identity. The research concludes with suggestions on possible grouping of elements essential to stimulate an enriching experience of place identity.